Adolescente egresso da fase: estudo de caso sobre o Programa RS Socioeducativo - Foppa, Giovana Mazzarolo (2011)
The present dissertation has as objective to analyze the implementation of the Programa RS Socioeducativo to the attendance of adolescents who come from the freedom restraining measure program of the Fundação de Atendimento Socioeducativo (FASE/RS). The program started in April, 2009, attending young people between 12 21 years old, aiming their social, cultural and familiar insertion, acting with the conception of net and co-responsability of the social actors. The investigation is based on a data collection and its documental analysis with the governmental institution Secretaria da Justiça e dos Direitos Humanos do Rio Grande do Sul, specifically in the coordinating of the Programa RS Socioeducativo, analyzing the number of young people attended by the program and its implications in their disconnection. Besides that, there are some information about the process of implementation of the estimated reports of the program done by active corporations, such as the project-executing agencies Fundação Pão dos Pobres de Santo Antônio and Instituto Pobres Servos da Divina Providência (IPSDP) Centro de Educação Profissional São João Calábria, as well as Relatório do Programa RS Socioeducativo provided by the coordinating of the Programa RS Socioeducativo. Individual interviews were also carried out with the adolescents who have concluded the social eucational program and the ones who were attended by the program but have come back to FASE/RS. Based on this research, we can say that the Programa RS Socioeducativo has qualified and attendance to the adolescent who gone out from FASE/RS. However, the precariousness in the health attendance done by the communitarian net, the low level of education of the adolescents, the family vulnerability, and the lack of connection between FASE/RS and the project-executing agencies were the obstacles which were found during the implementation.